189-(27*5)=z

Simple and best practice solution for 189-(27*5)=z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 189-(27*5)=z equation:


Simplifying
189 + -1(27 * 5) = z

Multiply 27 * 5
189 + -1(135) = z

Multiply -1 * 135
189 + -135 = z

Combine like terms: 189 + -135 = 54
54 = z

Solving
54 = z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-1z' to each side of the equation.
54 + -1z = z + -1z

Combine like terms: z + -1z = 0
54 + -1z = 0

Add '-54' to each side of the equation.
54 + -54 + -1z = 0 + -54

Combine like terms: 54 + -54 = 0
0 + -1z = 0 + -54
-1z = 0 + -54

Combine like terms: 0 + -54 = -54
-1z = -54

Divide each side by '-1'.
z = 54

Simplifying
z = 54

See similar equations:

| (38)(1.5)= | | 189-(27*5)= | | 5a+2b=13 | | 7x+172=180 | | 24x+4=2(12x+3) | | 4*7y= | | -7(5.8+9)=-84 | | 9y+6=39 | | 3x-2y+z=5 | | -11-8x=107-36x | | 3x+2x=-4x+4 | | 10y+9=-8y-9 | | 7y*4= | | x+4y+5z=11 | | 4(x+5)-(x-5)=19 | | (a^2-b^2)+2b*(a-b)=x | | 11x+45=180 | | -8=-20+2.3x | | (-7x-5y)+(3x+5y)= | | 5x+6=8x+3 | | 125m-75m+48000=50500-200m | | 49x^4-9x^2=0 | | h+15h= | | 5x-20+90=180 | | -(11-3a)=-5(1-a) | | 6x+168=3x+138 | | x^2-6=-5x | | 17h-47+6h=163 | | 3x-2+5x-20=90 | | 3x-2=-2+6 | | 3x-2+90+5x-20=180 | | -3c+6d=-15 |

Equations solver categories